Comparative analysis of laparoscopic and open enucleation for pediatric solid pseudopapillary neoplasm: a retrospective study - Zhou, Xiaogang; Sun, Yi; Chen, Jianlei; Cai, Peng; Zhao, Haowei; Jiang, Yuliang; Wang, Qi; Zhu, Menglei; Zhu, Jie; Zhu, Zhenwei (Frontiers in Pediatrics, 2025)
ObjectiveThis study compares the efficacy and safety of laparoscopic enucleation (LEN) vs. open enucleation (OEN) for pediatric solid pseudopapillary neoplasm (SPN) of the pancreas, aiming to provide clinical evidence for optimizing treatment strategies.MethodsA retrospective analysis evaluated clinical data from 20 pediatric SPN patients undergoing enucleation at the Children's Hospital of Soochow University, with 9 in the LEN group and 11 in the OEN group. Data included baseline characteristics, intraoperative parameters, postoperative outcomes, and complications.ResultsBaseline characteristics were comparable between groups (p > 0.05), with a median age of 11 years, and 75.0% female patients. The LEN group exhibited significantly reduced intraoperative blood loss (50.00 mL vs. 90.00 mL, p = 0.029) and postoperative pain duration (3.00 days vs. 5.00 days, p = 0.037) compared to the OEN group. No significant differences were observed in operative time (LEN: 240.00 min vs. OEN: 255.00 min, p = 0.790), hospital stay (LEN: 14.00 days vs. OEN: 15.00 days, p = 0.620), or pancreatic fistula incidence (LEN: 22.2% vs. OEN: 18.2%, p = 1.000). No grade C pancreatic fistulae, tumor recurrence, or pancreatic dysfunction occurred in either group.ConclusionLEN reduces blood loss and postoperative pain in pediatric SPN treatment with comparable safety to OEN. Larger-scale studies with extended follow-up durations are needed to confirm its long-term efficacy.